Thoracic Electrical Impedance Tomography—The 2022 Veterinary Consensus Statement - Brabant, Olivia A.; Byrne, David P.; Sacks, Muriel; Moreno Martinez, Fernando; Raisis, Anthea L.; Araos, Joaquin B.; Waldmann, Andreas D.; Schramel, Johannes P.; Ambrosio, Aline; Hosgood, Giselle; Braun, Christina; Auer, Ulrike; et al. (Frontiers in Veterinary Science, 2022)
Electrical impedance tomography (EIT) is a non-invasive real-time non-ionising imaging modality that has many applications. Since the first recorded use in 1978, the technology has become more widely used especially in human adult and neonatal critical care monitoring. Recently, there has been an increase in research on thoracic EIT in veterinary medicine. Real-time imaging of the thorax allows evaluation of ventilation distribution in anaesthetised and conscious animals. As the technology becomes recognised in the veterinary community there is a need to standardise approaches to data collection, analysis, interpretation and nomenclature, ensuring comparison and repeatability between researchers and studies. A group of nineteen veterinarians and two biomedical engineers experienced in veterinary EIT were consulted and contributed to the preparation of this statement. The aim of this consensus is to provide an introduction to this imaging modality, to highlight clinical relevance and to include recommendations on how to effectively use thoracic EIT in veterinary species. Based on this, the consensus statement aims to address the need for a streamlined approach to veterinary thoracic EIT and includes: an introduction to the use of EIT in veterinary species, the technical background to creation of the functional images, a consensus from all contributing authors on the practical application and use of the technology, descriptions and interpretation of current available variables including appropriate statistical analysis, nomenclature recommended for consistency and future developments in thoracic EIT. The information provided in this consensus statement may benefit researchers and clinicians working within the field of veterinary thoracic EIT. We endeavour to inform future users of the benefits this imaging modality and provide opportunities to further explore applications of this technology with regards to perfusion imaging and pathology diagnosis.